56 Are there inappropriate palliative patient deaths in emergency departments (ed)? a retrospective study looking at the deaths in a district general hospital ed. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Fox, Hannah; Doré, Matthew; Willis, Derek
Abstract : Introduction: Palliative patients sometimes present to emergency departments when dying and current policy aims to reduce such unnecessary admissions. This study provides a description of palliative care related deaths in an ED and an assessment of how many of these were preventable. Methodology: 32 consecutive deaths were reviewed in a district general ED department in Shropshire during 2016/2017. Death certification details, palliative status and DNACPR status were identified. We retrospectively judged whether their admission was potentially avoidable. Results: Epidemiology: Median age 83 years (range 40–95) 15 female patients (47%). Mode of death 12 patients died from respiratory pathology (37%), 6 from cardiac (18%), 6 from gastrointestinal (18%), 3 from infection (9%), 3 from stroke (9%), 1 from cancer (3%) and 2 were uncategorised. Frailty and palliative status Frailty and old age was documented on 10 death certificates (29%), dementia on 3 (9%). 4 patients (12%) had oncological disease. 2 patients (6%) were known to be palliative, 16 patients (50%) were not. There is uncertainty regarding the palliative status of the remaining patients and clarification using the gold standard framework is ongoing. 25 patients were DNACPR (81%). We believe 3 admissions were preventable (9%), 17 were unavoidable (53%) and the remaining 12 are unclear (38%). Conclusion: This study suggests that some palliative patients do present to ED and die, and that some of these admissions were avoidable. With ever increasing ED pressures we suggest it's imperative to understand the reasons, assess the scale, and find solutions to inappropriate palliative ED admissions.